Gender and age differences in polysomnography findings and sleep complaints of patients referred to a sleep laboratory - Silva,A. (2008)
Our objective was to examine the effet of gender on the sleep pattern of patients referred to a sleep laboratory. The data (questionnaires and polysomnographic recordings) were collected from a total of 2365 patients (1550 men and 815 women). The polysomnography permits an objective assessment of the sleep pattern. We included only polysomnography exams obtained with no more than one recording system in order to permit normalization of the data. Men had a significantly higher body mass index than women (28.5 ± 4.8 vs 27.7 ± 6.35 kg/m²) and had a significantly higher score on the Epworth Sleepiness Scale (10.8 ± 5.3 vs 9.5 ± 6.0), suggesting daytime sleepiness. Women had a significantly higher sleep latency than men, as well as a higher rapid eye movement (REM) latency. Men spent more time in stages 1 (4.6 ± 4.1 vs 3.9 ± 3.8) and 2 (57.0 ± 10.5 vs 55.2 ± 10.1) of non-REM sleep than women, whereas women spent significantly more time in deep sleep stages (3 and 4) than men (22.6 ± 9.0 vs 19.9 ± 9.0). The apnea/hypopnea and arousal indexes were significantly higher and more frequent in men than in women (31.0 ± 31.5 vs 17.3 ± 19.7). Also, periodic leg movement index did not differ significantly between genders, but rather differed among age groups. We did not find significant differences between genders in the percentage of REM sleep and sleep efficiency. The results of the current study suggest that there are specific gender differences in sleep pattern.